Increased Risk of Clopidogrel-Induced Gastric Mucosal Erosion in Elderly Chinese Men Harboring the ABCB1 3435T Allele - Duan L; Li M; Wang F; Cai Y; Li H; Zhou W; Li Y; Chen Q; Bai J; Liu H (Dove Medical Press, 2020)
Lei Duan, Man Li, Fan Wang, Yulun Cai, Huiying Li, Wenli Zhou, Yuerui Li, Qiang Chen, Jing Bai, Hongbin Liu Department of Geriatric Cardiology, National Clinical Research Center for Geriatric Diseases, The Second Medical Center of PLA General Hospital, Beijing 100853, People’s Republic of ChinaCorrespondence: Hongbin Liu Department of Geriatric CardiologyNational Clinical Research Center for Geriatric Diseases, The Second Medical Center of PLA General Hospital, 28 Fuxing Road, Beijing 100853, People’s Republic of ChinaTel +86 010 66876349Email liuhb301@sina.comBackground: It is uncertain whether long-term use of clopidogrel alone can cause gastric mucosal injury. This study aimed to evaluate the relationship between ABCB1 C3435T polymorphisms, which could affect the intestinal absorption of clopidogrel, and gastric mucosal erosion in elderly Chinese men who used clopidogrel alone.Methods: We selected 298 male patients (aged between 68.2 and 89.5 years, average age 78); 201 of them constituted the control group, and 97 constituted the case group. Patients taking clopidogrel alone who had undergone endoscopic screening for gastric erosion were analyzed for ABCB1 C3435T polymorphisms by a TaqMan assay.Results: The proportion of people carrying the ABCB1 3435T allele (n = 63, 64.9% vs n = 97, 48.3%, p = 0.007) was significantly higher in the case group than in the control group. After adjustments for significant factors were made, ABCB1 3435T allele carrier (OR 2.14, 95% CI 1.43– 3.84, p < 0.01) was found to be associated with gastric mucosal erosion in people who used clopidogrel alone.Conclusion: Carrying the ABCB1 3435T allele may be a useful genetic predictor for clopidogrel-induced gastric mucosal erosion in elderly Chinese men.Keywords: clopidogrel, polymorphism, single nucleotide, ABCB1 C3435T, gastric mucosa, risk factor